PECULIARITIES OF α1-ADRENOBLOCKERS USAGE IN PATIENTS WITH PREMATURE EJACULATION - Sarychev, Y.V. (World of Medicine and Biology, 2015)
The author has analyzed the literature and gives his own observations on α1-blockers usage in the treatment of patients with premature ejaculation. An array of studу consisted of 82 patients (divided into groups of tamsulosin, silodosin, doxazosin). Superselective α1-blockers, with a low number of systemic and local adverse events are recommended for use in patients with premature ejaculation.
Keywords: premature ejaculation; α1-adrenoblockers; treatment